Enhancing CO2 Adsorption on MgO: Insights into Dopant Selection and Mechanistic Pathways - Shunnian Wu; W. P. Cathie Lee; Hashan N. Thenuwara; Xu Li; Ping Wu (Biomimetics)
Inspired by our recent success in designing CO2-phobic and CO2-philic domains on nano-MgO for effective CO2 adsorption, our ongoing efforts focus on incorporating dopants into pristine MgO to further enhance its CO2 adsorption capabilities. However, a clear set of guidelines for dopant selection and a holistic understanding of the underlying mechanisms is still lacking. In our investigation, we combined first-principles calculations with experimental approaches to explore the crystal and electronic structural changes in MgO doped with high-valence elements (Al, C, Si, and Ti) and their interactions with CO2. Our findings unveiled two distinct mechanisms for CO2 capture: Ti-driven catalytic CO2 decomposition and CO2 polarization induced by Al, C, and Si. Ti doping induced outward Ti atom displacement and structural distortion, facilitating CO2 dissociation, whereas C doping substantially bolstered the electron donation capacity and CO2 adsorption energy. Pristine and C-doped MgO engaged CO2 through surface O atoms, while Al-, Si-, and Ti-doped MgO predominantly relied on dopant–O atom interactions. Our comprehensive research, integrating computational modeling and experimental work supported by scanning electron microscopy and thermal gravimetric analysis, confirmed the superior CO2 adsorption capabilities of C-doped MgO. This yielded profound insights into the mechanisms and principles that govern dopant selection and design.